Prevention of Dengue Hemorrhagic Fever (DHF) Associated with the Aedes aegypti Larvae Presence based on the Type of Water Source - Nurul Hidayah; Iskandar Iskandar; Zainal Abidin (Journal of Tropical Life Science, 2017)
Aedes aegypti is the vector of Dengue Hemorrhagic Fever (DHF) disease. Containers are breeding places for DHF vector and the most commonly found larvae in the bath water containers. The presence of Aedes aegypti larvae in a container could be affected by the type of water source besides the container’s color, material, location, lid existence and the container’s drain frequency. This study was conducted to determine the associate of water source type with larvae presence and the additional factors. This study used observational analytic with case control design. The case group consisted of households using well water and the control group consisted of households using tap water with a sample size of 130 households for each group. The sample was collected by proportional random sampling in five villages. The data was analyzed using a regression logistic test. The significant variables associated with the presence of larvae were the water source type (OR=1.923), container’s color (OR=2.345), container’s location (OR=2.241), container’s lid existence (OR=2.122) and the container’s drain frequency (OR=2.260). This study did not consider the significant association of the container’s material. The dominant variable associated with the presence of larvae was the container’s drain frequency which was controlled by the water source type, container’s color and container’s location.